'We are still here': The impacts of street music and street art during the 2020 London lockdowns. Issue 2 (1st November 2021) - Barnes, Jonathan
This article summarises the impacts of a spontaneous arts initiative involving the residents of eight London streets during the 2020 lockdowns. A local arts organization devised small-scale, informal street music projects that were evaluated by the residents themselves. Responses suggested that such events had a strong positive impact on the feelings of community. Common responses included reaffirming the importance of local cohesion, recognizing music as an accessible means of developing new connections in 'distanced' conditions and a new appreciation of family togetherness. Those involved suggested that researchers could learn much about the characteristics of cohesive, supportive communities from similar initiatives. The project confirmed that more research was needed on the role schools could play in bringing communities together and how music can be used to build bridges between school and community. Feedback raised questions about the absence of children's voices in post-COVID-19 planning for 'the recovery curriculum'.